Property rights and transaction costs: The role of ownership and organization in German public service provision - Maria Friese; Ulrich Heimeshoff; Gordon Klein (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
This paper provides evidence that ownership and organization matters for the efficiency of provision of public services. In particular, we find that pure private ownership is more efficient than pure public ownership, and public ownership is more efficient than mixed ownership. The delegation of management in different legal forms also has an impact, highlighting the importance of the design of the government-operator relationship. We apply a structural approach of production function estimation ensuring precise determination of total factor productivity for a panel of German refuse collection firms between 2000-2012. We project total factor productivity estimates on ownership and organization. Our results are in line with the trade-offs implied by the property rights literature and provide important policy implications regarding the organization of public service provision.
Keywords: D2; H1; L3; 330; productive efficiency; refuse collection; public service